Simultaneous Fictions: Reading Form and Attention in the Contemporary Novel - Waalkes, Rebekah. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of English.; Advisor: John Lurz.; Committee: Lee Edelman, Ichiro Takayoshi, and Merve Emre.; Keyword: Literature.